HPB P66 Resection margin status, five-year recurrence and five-year survival in ampullary adenocarcinoma and cholangiocarcinoma patients who undergo pancreatoduodenectomy. (7th December 2022) - Russell, Thomas; Labib, Peter; Aroori, Somaiah
Abstract: Background: Patients with a suspected early cancer affecting the periampullary region may be offered resection in the form of pancreatoduodenectomy (PD) if they are a suitable candidate. Whilst this offers some patients a potential cure, the operation is high-risk and disease recurrence is common. Patients who are found to have ampullary adenocarcinoma (AA) or cholangiocarcinoma (CC) on their postoperative histology are known to have relatively favourable oncological outcomes if their resection margins are clear. This study aimed to investigate the correlation between a positive margin and both five-year recurrence and five-year survival. Methods: Data was extracted from the Recurrence After Whipple's (RAW) study, a multicentre retrospective cohort study of outcomes following pancreatoduodenectomy performed for pancreatic head malignancy (29 centres in 8 countries, n=1, 484). Patients with postoperative histology suggestive of AA and CC were identified and compared to one another by their resection margin status. Five-year recurrence and survival rates were compared using Fisher's exact test. Results: A total of 394 patients had AA (26.5%) and 364 of these (92.4%) had their resection margin status recorded. Of these, 295 (81.0%) had no positive margins (R0), 69 (19.0%) had at least one positive margin (R1) and zero (0.0%%) had an incomplete resection (R2). Patients with R0 disease had lower five-year recurrence (41.4% vs 63.8%, p=0.0012) and higher five-year survival rates (59.0% vs 30.4%, p<0.00001) compared to those with R1 disease. A total of 205 patients had CC (13.8%) and 202 of these (98.5%) had their resection margin status recorded. Of these, 113 (55.9%) had no positive margins (R0), 86 (42.6%) had at least one positive margin (R1) and three patients (1.5%) had an incomplete resection (R2). Patients with R0 disease had lower five-year recurrence (60.2% vs 76.7%, p=0.015) and higher five-year survival rates (38.1% vs 15.1%, p=0.0004) compared to those with R1 disease. Conclusions: In our multicentre study, the majority of patients who underwent PD for AA or CC had no positive resection margins. These patients had significantly improved five-year outcomes.